Transformative Citizenship Education: Strengthening Civic Engagement to Empower People with Disabilities - Nanggala, Agil; Suryadi, Karim; Darmawan, Cecep; Saepudin, Epin (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
Disability in Indonesia and globally remains closely associated with systemic discrimination, as legal protections alone have not been sufficient to dismantle stigma rooted in ableism, isolation, and exclusion. Citizenship education, when integrated with disability studies, offers a constructive framework for promoting inclusivity and civic participation in line with the social model of disability, which challenges the medical and charity models that perpetuate marginalization. This study aims to analyse how disability studies can be integrated into non-formal citizenship education to strengthen civic engagement that empowers people with disabilities and reflects transformative citizenship and civic empowerment. This research used a qualitative descriptive method with purposive and snowball sampling. Data were collected through interviews and observations with people with disabilities and their families, philanthropic communities, election officials, disability service units in higher education, and experts in citizenship education, health, public policy, and Pancasila studies. The findings show that empowerment initiatives—such as philanthropic programs, service learning, and inclusive election practices—are present but remain fragmented, ceremonial, and constrained by weak inter-sectoral collaboration. Nonetheless, the integration of service learning and pentahelix collaboration strengthens civic competence, youth leadership, and inclusive participation in communities. This study concludes that Indonesia’s Pancasila citizenship model provides a strong normative foundation for embedding disability empowerment in citizenship education. Its contribution lies in expanding citizenship education theory through disability perspectives while offering practical strategies for cross-sectoral collaboration. The implication is the need for sustainable policies and civic practices to transform legal guarantees into inclusive social justice.  Disabilitas di Indonesia maupun global masih terkait dengan diskriminasi sistemik, karena perlindungan hukum belum cukup untuk menghapus stigma yang berakar pada ableisme, isolasi, dan eksklusi. Pendidikan kewarganegaraan yang terintegrasi dengan kajian disabilitas menawarkan kerangka untuk memperkuat inklusivitas dan partisipasi kewargaan sesuai model sosial disabilitas, yang menolak model medis dan amal yang sering melanggengkan marginalisasi. Penelitian ini bertujuan menganalisis bagaimana kajian disabilitas dapat diintegrasikan ke dalam pendidikan kewarganegaraan non-formal untuk memperkuat keterlibatan kewargaan yang memberdayakan penyandang disabilitas serta merefleksikan kewargaan transformatif. Metode yang digunakan adalah kualitatif deskriptif dengan teknik purposive dan snowball sampling. Data diperoleh melalui wawancara dan observasi terhadap penyandang disabilitas dan keluarga, komunitas filantropi, penyelenggara pemilu, unit layanan disabilitas di perguruan tinggi, serta para ahli pendidikan kewarganegaraan, kesehatan, kebijakan publik, dan Pancasila. Hasil menunjukkan bahwa inisiatif pemberdayaan—seperti program filantropi, service learning, dan praktik pemilu inklusif—sudah ada, namun masih terfragmentasi, seremonial, dan terkendala lemahnya kolaborasi lintas sektor. Meski demikian, integrasi service learning dan kolaborasi pentahelix terbukti memperkuat kompetensi kewargaan, kepemimpinan pemuda, dan partisipasi inklusif di masyarakat. Kesimpulannya, model kewarganegaraan Pancasila memberi dasar normatif kuat untuk mengintegrasikan pemberdayaan disabilitas dalam pendidikan kewarganegaraan. Kontribusi penelitian ini adalah memperluas teori pendidikan kewarganegaraan melalui perspektif disabilitas serta menawarkan strategi praktis kolaborasi lintas sektor. Implikasinya, diperlukan kebijakan berkelanjutan dan praktik kewargaan kolaboratif untuk mewujudkan keadilan sosial yang inklusif.